STRUKTUR KOMUNITAS SERANGGA POLINATOR DI KEBUN BUAH AGRIBISNIS FAKULTAS PERTANIAN UNIVERSITAS RIAU - Suwondo "; Elya Febrita; Kurnia Khairi (Biogenesis, 2016)
ABSTRACT The aim of this research was to determine community structure of pollinator insects in fruit garden Agribusiness Agriculture Faculty University of Riau in March to April 2015. The research was conducted with determining the location of the observation by purposive sampling to establish the location of the observation at 5 fruit garden Agribusiness Agriculture Faculty University of Riau. Biological parameters observed that the abundance of species, dominance index and preferences visits, while the environmental physical parameters include temperature, humidity and light intensity. The results showed the highest relative abundance is Apis cerana, insect pollinators dominance index was low (0,189 to 0,363) and the highest preference insect pollinators in the afternoon (15:00 to 17:00). Keywords: Community structure, Insect pollinators.